(3JZQjO GdLejdI defGOeI GdYbjdIs - (3HQgGf GdOjf EHQGgje Hf YeQ GdLYHQis; (3GdTGWHj GdebQF GdVQjQ , CHh eMeO,J (B590 (3g` s
(3ChdgG (B:s
(3hHYO adeG cGf GdeXe GdeSei HGdYbjdI ef CLd eG Cda ai Yde GdQSe hCaVd hcGf TQM GdLYHQi GdeSei HGdLejdI ef CMSf TQhMgG s
(3BNQgG (B:s
(3hYf GdSMGH fXQ GdHQb GdeVGMcI eSJbjekG efgG s
(3GdfSNI HgG MhGTs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B180 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B110s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1159s
Keywords: (3GdbQGAGJ hGdJLhjOs